Lacan and the Benedictines - John Gale (EJP import test, 2018)
Summary: In this paper the author considers, by a careful reading of the Regula Benedicti (RB) and its sources, the claim by Michel de Certeau that some of Lacan’s ideas are based on Benedictine monasticism. As well as the four concepts that de Certeau identifies (analyst as monk; master; school; and work-as-speech) the author also considers whether four additional notions (desire; the uniqueness of the subject; nothingness; and empty speech)—the latter two of which may have been mediated to Lacan by Heidegger—which come from the Regula Benedicti.
Keywords: De Certeau; Heidegger; Lacan; Monastic; Regula Benedicti